Shadows of Swanford Abbey [large type] - Klassen, Julie, 1964- (Thorndike Press large print Christian romance series., 2022)
"In pursuit of an author who could help get her brother published, Rebecca Lane stays at Swanford Abbey, a grand hotel rumored to be haunted. It is there she encounters Sir Frederick-the man who broke her heart. When a mysterious death occurs, Rebecca is one of the suspects, and Fredrick is torn between his feelings for her and his search for the truth"--